Optimization of Traffic Safety Education (Dikmas Lantas) by the Kamsel Unit to Reduce Traffic Accident Rates in Polresta Pati - Rs, Akbar (Indonesian Journal of Police Studies, 2024)
The Kamsel Unit through Dikmas activities has a very important role in carrying out pre-emptive tasks by the Traffic Unit, namely by reducing the number of traffic accidents at Polresta Pati before the incident occurs and with the aim of identifying and describing the implementation of Dikmas Then the Kamsel Unit in order to reduce the number of traffic accidents. traffic, so that it can reduce the number of traffic accidents at Polresta Pati. In writing this final project, several concepts and theories are used as a knife for analysis, namely the concept of Traffic Dikmas, the concept of traffic accidents, the concept of optimization which refers to applicable regulations, then using management theory and S.W.O.T. The approach used is qualitative, namely field research, with data collection techniques using observation and interview techniques. The analysis was carried out using data reduction, data presentation and drawing conclusions. Based on the results of research that has been carried out that the implementation of Dikmas Then by the Kamsel Unit has not met expectations, it can be seen in the planning, organizing, implementation and control carried out, and also in organizational resources that are also not yet qualified, and is indicated by a spike in the number of traffic accidents 2022 compared to the previous year. It can be concluded that in terms of the implementation of Dikmas Then activities carried out by the Satlantas Polresta Polresta Unit in Pati to reduce the number of traffic accidents at Polresta Pati it can still be improved by taking into account several factors that influence the initial conditions and also in the methods and organizational resources carried out by South Kamal Unit in carrying out Dikmas Then activities in the field.